Examining the relationship between ranchers' demographic profile and success of small ruminant farming - Yusoff, Melissa Alina; Man, Norsida; Mohd Nawi, Nolila (Universiti Putra Malaysia Press, 2018)
Small ruminant (goat and sheep) farming is one of the emerging farming sectors that has a lot of potential that waits to be developed. It is constantly supported by various Malaysian government agencies in order to increase the self-sufficiency level of ruminant food. Several factors directly influence ranch farming and could contribute to the marginal profits. Hence, some ranchers are successful, while other ranchers facing similar circumstances are not. Therefore, the aim of this study is to determine the relationship between ranchers' demographic profile and the factors that contribute to success in small ruminant farming. The primary data was collected via face-to-face interviews using a well-structured questionnaire. The collected data were analysed using both descriptive and chi-square analysis. The results showed that age, marital status, educational attainment and level of experience have a significant relationship with the factors of success in this type of farming. The Department of Veterinary Services as the agency responsible for this type of farming needs to take action and make the necessary improvements, taking into consideration the ranchers' demographic profile, especially their age, marital status, educational attainment and level of experience in order to design training and innovative farm visits, among other initiatives. This will enable ranchers to reach higher levels of success in small ruminant farming. This in turn will enhance and boost the livelihood activities of the ranchers and subsequently develop the small ruminant industry in Malaysia.